2011
DOI: 10.1002/prs.10499
|View full text |Cite
|
Sign up to set email alerts
|

Explosion of fixed roof atmospheric storage tanks, part 2: Analytical methods to assess safety distances

Abstract: Many flammable products are stored in large tanks at atmospheric pressure. Ignition of a hydrocarbon–air mixture in such tanks can lead to an explosion and cause lethal casualties or damage to the surrounding facilities and buildings. To apprehend this, safety distances for humans, structures, and equipments need to be defined. Several simple methodologies have been set up to estimate safety distances in case of an atmospheric storage tank explosion. After giving an overview of past accidents [1], this second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Table 8 compares energies obtained with analytical methods, previously described in Ref. 2, and the energy calculated using FLACS. Results largely differ depending on the methodology used (from 69 to 1,247% of E FLACS for the compact tank; from 23 to 420% of E FLACS for the elongated tank).…”
Section: Conversion Of Energymentioning
confidence: 99%
See 3 more Smart Citations
“…Table 8 compares energies obtained with analytical methods, previously described in Ref. 2, and the energy calculated using FLACS. Results largely differ depending on the methodology used (from 69 to 1,247% of E FLACS for the compact tank; from 23 to 420% of E FLACS for the elongated tank).…”
Section: Conversion Of Energymentioning
confidence: 99%
“…FLACS simulations were performed to assess safety distances for two types of tanks: compact tank ( H / D < 1): D = 60 m; H = 14 m (same case as in Ref. 2); P F = 0.5 barg (Figures 6a–6c); elongated tank ( H / D > 1): D = 9 m; H = 14 m (same case as in Ref. 2); P F = 1 barg (Figures 7a–7c). …”
Section: Pressure Wave Propagationmentioning
confidence: 99%
See 2 more Smart Citations
“…No satisfactory approach for evaluating the parameters of flying fragments has yet been developed. A literature survey showed that much effort was dedicated to explosive loading of structures [1] as well as to processes connected with pressure vessels and bursting tanks [2]. Only a little information was found concerning the problem of secondary fragments caused by accidental explosions.…”
Section: Introductionmentioning
confidence: 99%